Sensitivity of carbon emission estimates from indirect land-use change - Dumortier, Jerome; Hayes, Dermot J.; Carriquiry, Miguel; Dong, Fengxia; Du, Xiaodong; Elobeid, Amani; Fabiosa, Jacinto F.; Tokgoz, Simla (Wiley, 2011)
An agricultural projection and greenhouse gas model are used to assess the impact of global cropland expansion on carbon emissions and the sensitivity of those estimates to modifications in assumptions concerning idle cropland, the degree of refinement in carbon coefficients, market responses, and yield increase. The results indicate that the impact of cropland expansion on carbon emissions is extremely sensitive to model assumptions. This is particularly true with respect to the price‐induced yield response. Given the available knowledge, it is very difficult to narrow the range of reasonable parameter values to tighten the set of results to a level that would allow robust policy conclusions.